Edukasi “Isi Piringku” pada Remaja dalam Upaya Cegah Stunting di SMA Islam Al Falah Kota Jambi - Hatussaadah, Siti Fati; Chandra, Filius (Jurnal Abdimas Kesehatan (JAK), 2025)
Stunting during adolescence will affect psychomotor development, fine motor skills and neurosensory integration, the level of intelligence and the lack of competitiveness that children have in the fields of development and the economy. Nutrition in adolescents determines the optimization of learning, maturation of thought patterns and optimization of the work of organ systems. A teenager's diet will determine the amount of nutrients they obtain for their growth and development. "Isi Piringku" explains what is needed in a portion of food that can meet nutritional needs, in one portion of food there must be half the plate filled with vegetables and fruit, the other half filled with a source of protein (both vegetable and animal), in the right proportions. more than carbohydrates. Nutrition education regarding "Isi Piringku" for teenagers is one of the efforts to prevent stunting by implementing a healthy diet and meeting daily nutritional needs. At Al Falah Islamic High School, Jambi City, priority problems are still found, namely that the majority of teenagers still do not know about the terms "Isi Piringku" and the Message of Balanced Nutrition. There are still teenagers who adopt unhealthy eating patterns amidst busy school activities so that their nutritional needs are not met. The aim of this community service activity is to provide "Isi Piringku" Nutrition Education to Teenagers in Efforts to Prevent Stunting. The series of activities will start from March 2023 to September 2023 at Al Falah Islamic High School, Jambi City. Participants who attended were estimated at 40 people. The material was presented using power point for ± 90 minutes including a question and answer session with the participants. Before and after education, a pretest and posttest are given which are carried out by activity participants. The results obtained were a change in the average pretest and posttest knowledge, namely 7 (78 to 85). This activity has improved participants’ knowledge about healthy eating patterns as an effort to prevent stunting. It is hoped that similar education can be carried out sustainably in the future so that adolescents become increasingly able to adopt balanced nutrition practices in their daily lives